LINQ programming [ - Mayo, Joseph (New York : McGraw Hill, 2009)
A hands-on guide to LINQ, Microsoft's revolutionary new programming technology
1. Introducing LINQ -- 2. Using LINQ to objects -- 3. Handling LINQ to SQL with visual studio -- 4. Working with ADO.NET through LINQ to DataSet -- 5. Programming objects with LINQ to entities -- 6. Programming objects with LINQ to XML -- 7. Automatically generating LINQ to SQL code with SqlMetal -- 8. Digging into expression trees and lambdas -- 9. Constructing new code with extension methods -- 10. Building a custom LINQ provider: introducing LINQ to Twitter -- 11. Designing applications with LINQ -- 12. Concurrent programming with Parallel LINQ (PLINQ)
Includes index
Keywords: Microsoft .NET Framework; Query languages (Computer science)